Modulation of the hepatic RANK-RANKL-OPG axis by combined C5 and CD14 inhibition in a long-term polytrauma model - Li, Yang; Horst, Klemens; Greven, Johannes; Mert, Ümit; Lupu, Ludmila; Palmer, Annette; Doerfer, Lena; Zhao, Qun; Zhang, Xing; Halbgebauer, Rebecca; Ignatius, Anita; Marzi, Ingo; et al. (Frontiers in Immunology, 2024)
BackgroundPolytrauma and hemorrhagic shock can lead to direct and indirect liver damage involving intricate pathophysiologic mechanisms. While hepatic function has been frequently highlighted, there is minimal research on how the receptor activator of the NF-κB (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) system is regulated in the liver following trauma. Furthermore, cross-talking complement and toll-like-receptor (TLR) systems can contribute to the posttraumatic response. Therefore, we investigated the hepatic consequences of polytrauma focusing on the RANK-RANKL-OPG axis, and evaluated the effects of a dual blockade of complement factor C5 and TLR-cofactor CD14 on hepatic features.MethodsThe established pig model of polytrauma (PT) and hemorrhagic shock included pulmonary contusion, hepatic dissection, and bilateral femur fractures, surgically addressed either by external fixation (Fix ex) or intramedullary nailing (Nail). Four groups were investigated: 1) sham animals; 2) PT treated by Fix ex (Fix ex); 3) PT by Nail (Nail); or 4) PT by Nail plus combined C5/CD14 inhibition (Nail+Therapy). Serum samples were obtained between 0 - 72 h, and liver samples at 72 h after PT. Liver tissues were histologically scored and subjected to RT-qPCR-analyses, immunohistochemistry and ELISAs to evaluate the posttraumatic hepatic response with a focus on the RANK-RANKL-OPG system.ResultsFollowing PT, the liver injury score of the Nail+Therapy group was significantly lower than in the Fix ex or Nail group without immunomodulation (p<0.05). Similarly, the degree of necrosis, lobular stasis, and inflammation were significantly reduced when treated with C5/CD14-inhibitors. Compared to the Nail group, AST serum concentrations were significantly decreased in the Nail+Therapy group after 72 h (p<0.05). PCR analyses indicated that RANK, RANKL, and OPG levels in the liver were increased after PT in the Nail group compared to lower levels in the Nail+Therapy group. Furthermore, liver tissue analyses revealed increased RANK protein levels and cellular immunostaining for RANK in the Nail group, both of which were significantly reduced in the case of C5/CD14-inhibition (p<0.05).ConclusionFollowing experimental PT, dual inhibition of C5/CD14 resulted in altered, mainly reduced hepatic synthesis of proteins relevant to bone repair. However, a comprehensive investigation of the subsequent effects on the liver-bone axis are needed.